UiT-researchers' attitudes and practices towards open access publication : lessons learnt for improving self-archiving in institutional repository - Msomphora, Mbachi Ruth (2021)
Objective. Using The Munin Repository at UiT The Arctic University of Norway as a case study, a survey was conducted among the UiT researchers to examine their attitudes and practices towards the repository and towards open access (OA) publications. Methods. The survey questionnaire was sent to all employees at UiT between August and October 2016, but only academic staff in research positions, including PhD students, were selected for the analysis. 200 researchers responded to the survey. Results. The study found that researchers are supportive of the principle of OA but are less keen on contributing to their institutional repositories for a range of reasons. These include the process being quite a hassle, academics' uncertainty over certain legal, copyright and peer review issues, prestige issues, and uncertainty over the appropriate version to deposit or self-archive. Contribution. The statistical results can be used by readers as benchmarks to compare with their own institution's figures. Conclusively, the study found that more than 90% of the researchers agreed with the OA principles, but still 54% of UiT researchers did not archive their research documents in The Munin Repository.